2021
DOI: 10.3389/fped.2021.722385
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Gestational Weight Gain With Left Ventricle Geometry and Function in Offspring at 4 Years of Age: A Prospective Birth Cohort Study

Abstract: Background: Maternal gestational weight gain (GWG) may be associated with cardiovascular diseases in the offspring from childhood to adulthood. We aimed to investigate the association between maternal GWG and the left ventricle (LV) geometry and function in the offspring, and explore the influence of the intrauterine environment on early childhood cardiac change.Methods: Data of 981 mother-offspring pairs from the Shanghai Birth Cohort was used. Maternal pre-pregnancy weight and height, weight in the first tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Five of thirteen (39%) articles excluded women with GDM. Two studies included women with diabetes, but the incidence of type 1 or 2 diabetes and GDM was not mentioned among women with obesity or controls [ 33 , 41 ]. Two other articles did not mention type 1 or 2 diabetes and GDM [ 31 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of thirteen (39%) articles excluded women with GDM. Two studies included women with diabetes, but the incidence of type 1 or 2 diabetes and GDM was not mentioned among women with obesity or controls [ 33 , 41 ]. Two other articles did not mention type 1 or 2 diabetes and GDM [ 31 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included studies. Six articles reported on outcomes in fetuses (n = 1483) [28][29][30][31][32][33], three articles on outcomes in neonates (n = 187) [34,35,39], three on outcomes in infants (children <1 year of age) (n = 234) [34][35][36] and three articles reported on outcomes in children older than 1 year of age (n = 6966) [38,40,41]. No articles reported on cardiac structure or function in adolescents or adults born to women with obesity.…”
Section: Plos Onementioning
confidence: 99%
“…LV interventricular or posterior wall thickness, internal diameter, volume in systole and diastole (IVSs, IVSd, LVPWs, LVPWd, LVIDs, LVIDd, ESV and EDV), ejection fraction (LVEF), and shorten fraction (LVFS) were measured. Relative wall thickness (RWT), LV mass (LVM), LVM index (LVMI), E/A ratio, Tei index, and global peak longitudinal strain (GLS) were measured as previously described [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sex-specific 95th percentiles (P95th) of LVMI (male: 33.76 g/m 2.7 and female: 33.24 g/m 2.7 ) were derived from our own cohort. LV hypertrophy (LVH) was defined as LVMI ≥ the sex-specific P95th of LVMI [ 26 , 30 ]. All examinations were performed by experienced operators.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies by our team have found intrauterine environmental exposure during pregnancy to be correlated with the development of fetal immune system, cardiovascular system, and physical capacity. [121][122][123][124] Excessive maternal weight gain during pregnancy, especially in the second and third trimesters, was associated with thickening of the interventricular septum and was a risk factor for left ventricular hypertrophy in children aged 4 years. [124] Children with a high birthweight had an increased risk of structural changes to the left ventricle at age 4 years, and boys had a higher risk of left ventricular hypertrophy, while girls did not.…”
Section: The Construction Of Our Translational Medicine Platformmentioning
confidence: 99%